CCD photometry of some areas around the open cluster M45 - Savushkin, A.A.; Shlyapnikov, A.A. (Advances in Astronomy and Space Physics, 2012)
We present the results of photometric studies in some areas around the open star cluster M 45. Observations were carried out on January-March 2012. About 600 images were obtained in the V band (Johnsons system). Centres of the observed areas correspond to the maximum concentration of stars with the solar-type activity. Using the V-band magnitude values from the GTSh10 catalogue we analysed the flare activity of the stars. The catalogue of observations with the shared access through the Aladin interface was compiled.